Perbedaan Sebelum Dan Sesudah Penggunaan Pendekatan Metakognitif Berbantuan Canva Terhadap Kemampuan Pemecahan Masalah Siswa - Ambar Indraswari; Lisa Virdinarti Putra (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: This study aims to determine the difference between before and after using the metacognition approach using canva application towards problem solving ability of class IV elementary school students on KPK and FPB materials This study is a quantitative research with an experiment method. The experiment method used is the quasi-experimental design with the nonequivalent control group design. The population in this study were students of Public Elementary School Ampel 2 and Public Elementary School Urutsewu 3, who was still in one group. The samples in this study were the 4th grade students of Public Elementary School Ampel 2 and the 4th grade students of Public Elementary School Urutsewu 3. The data analysis technique used by researcher are normality tests, homogeneous tests, and independent sample t test. The results showed that there are differences in using metacognition approach with using canva application to experiment classes and metacognition approach only to control classes towards problem solving ability of class IV elementary school students on KPK and FPB materials, proven by the level of significance was 0,044 < 0,05 used independent sample t test. The results of this study can be concluded that the metacognition approach using canva application given effect toward towards problem solving ability of class IV elementary school students on KPK and FPB materials. Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan sebelum dan sesudah menggunakan pendekatan metakognitif berbantuan canva terhadap kemampuan pemecahan masalah siswa kelas IV SD pada materi KPK dan FPB. Jenis penelitian ini adalah penelitian kuantitatif dengan metode eksperimen. Jenis metode eksperimen yang digunakan ialah quasi experimental design dengan bentuk desain nonequivalent control group design. Populasi dalam penelitian ini adalah siswa SD N 2 Ampel dan siswa SD N 3 Urutsewu yang masih berada dalam satu gugus, kemudian untuk sampel dalam penelitian ini adalah siswa kelas 4 SD N 2 Ampel dan siswa kelas 4 SD N 3 Urutsewu. Teknik analisis data dengan uji normalitas, uji homogenitas, dan uji independent sample t test. Hasil penelitian penunjukkan bahwa terdapat perbedaan penggunaan pendekatan metakognitif berbantuan canva untuk kelas eksperimen dan pendekatan metakognitif saja untuk kelas kontrol terhadap kemampuan pemecahan masalah siswa kelas IV pada materi KPK dan FPB, dibuktikan dengan taraf signifikansi 0,044 < 0,05 menggunakan uji independent sample t test. Hasil penelitian ini dapat disimpulkan bahwa pendekatan metakognitif berbantuan canva berpengaruh terhadap kemampuan pemecahan masalah siswa kelas IV pada materi KPK dan FPB.